plz plz plz help me
proove kerna hai
Attachments:
![](https://hi-static.z-dn.net/files/d80/af28c6c650cf5019ac89a62da2ab669a.jpg)
Answers
Answered by
1
Step-by-step explanation:
=4cosx*cos(60-x)*cos(60+x)
=4cosx*(cos60*cosx+sin60*sinx)* (cos60*cosx-sin60*sinx)
= 4cosx*(cosx/2 + 3½sinx/2)*(cosx/2 - 3½sinx/2)
= 4cosx*(cos²x/4 - 3sin²x/4)
= 4cosx*(cos²x - 3sin²x)/4
= cosx (cos²x - 3sin²x)
= cosx (cos²x - 3(1-cos²x))
= cosx (cos²x - 3 + 3cos²x)
= cosx (4cos²x - 3)
= 4cos³x - 3cosx
( cos3x = 4cos³x - 3cosx)
= cos3x (hence proved)
Similar questions